A comparison of selected Western and Chinese smart governance: The application of ICT in governmental management, participation and collaboration. (November 2018) - Lin, Yanliu
Abstract: There has been increasing scholarly interest in the concepts and practices of smart governance. However, there is a lack of comparative studies of smart governance in different institutional contexts. This study develops a framework for comparing smart governance in different institutional and technological contexts. Comparative and discourse analyses are conducted to understand the similarities and differences of smart governance practices in selected Western countries and China. A key finding of this study is that different institutions have largely affected smart governance strategies, arrangements and outcomes. Smart governance is tightly linked with e-governance and e-democracy in some Western countries, while it officially emphasizes smart management and service in China. A common aspect is that the increasing use of social media, smartphones, portals, crowdsourcing platforms, and planning support systems have generally promoted smart governments and services, e-participation, and wider collaboration through both top-down and bottom-up approaches. This could lead to gradual changes in government organizations, new relations between governments, the private sector and citizens, and improvements in the city. Highlights: This study develops a framework for understanding smart governance in different contexts. It compares the similarities and differences of smart governance in selected Western countries and China. Different institutions have affected smart governance strategies, arrangements and outcomes. Smart governance is linked with e-democracy in Western countries, while emphasizing smart management in China. New technologies have promoted smart governments and services, e-participation, and wider collaboration.